FEATURES OF ADAPTATION OF FUTURE SPECIALISTS OF FIRE AND RESCUE SERVICE TO THE CONDITIONS OF PROFESSIONAL ACTIVITY - V.M. Pokalyuk (Освітній вимір, 2009)
The problem of cadets' adaptation to the conditions of professional activity of fire-resque servise.